A companion to Buddhist philosophy - Emmanuel, Steven M. (Chichester, West Sussex, United Kingdom : Wiley-Blackwell, 2013)
'A Companion to Buddhist Philosophy is the most comprehensive single volume on the subject available; it offers the very latest scholarship to create a wide-ranging survey of the most important ideas, problems, and debates in the history of Buddhist philosophy. Encompasses the broadest treatment of Buddhist philosophy available, covering social and political thought, meditation, ecology and contemporary issues and applications Each section contains overviews and cutting-edge scholarship that expands readers understanding of the breadth and diversity of Buddhist thought Broad coverage of topics allows flexibility to instructors in creating a syllabus Essays provide valuable alternative philosophical perspectives on topics to those available in Western traditions'--
'Encompasses the broadest treatment of Buddhist philosophy available, covering social and political thought, meditation, ecology and contemporary issues and applications'--
Conceptual foundations -- Major schools of Buddhist thought -- Themes in Buddhist philosophy -- Buddhist meditation -- Contemporary issues and applications.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Buddhist philosophy; Buddhist philosophy; PHILOSOPHY -- Eastern; Buddhist philosophy; Electronic books